2600 phrases for setting effective performance goals : ready-to-use phrases that really get results - Falcone, Paul (American Management Association, 2012)
As a manager, you aren't truly successful unless your employees are as well. But their success depends on you. Complete with handy bonuses like an individualized development plan (IDP) tool, 2600 Phrases for Setting Effective Performance Goals teaches readers to not only set expectation on the basics like attendance, attitude, teamwork, and time management--you'll learn how to craft goals that internally motivate your employees to achieve phenomenal results.